Agronomic characterization of amaranth for cultivation in the Brazilian Savannah - Teixeira, Danielly Leite; Spehar, Carlos Roberto; Souza, Luiz Augusto Copati (Pesquisa Agropecuaria Brasileira, 2003)
The objective of this work was to characterize and evaluate 48 accessions of three species of amaranth (Amaranthus caudatus L., A. cruentus L., and A. hypochondriacus L.) for cropping systems in the Brazilian Savannah. A preliminary test was carried out in the glasshouse for seven descriptors and the accessions with suitable phenotypes were selected for field trials. The experimental design was that of randomized blocks, with three repetitions. The material selected presented agronomic desirable characteristics such as prickle absence, straight growing habit and presence of inflorescense. These experiments were carried out in Planaltina, DF, during the dry season, under irrigation, for two years. Generally, the accessions flowered 45 days after emergence and the plants were harvested after 90 to 100 days. The data were analyzed for principal components. The two first components responded for 92.18% of the variation. Three groups of similarity were established, using the nearest neighbor method that explained 86% of total variation. Independently of origin, the potential for cultivation of grain amaranth in the Savannah was expressed by the performance of some genotypes. Amaranth can be exploited for cultivation in the Brazilian Savannah and it will contribute for diversification of cropping systems.
Keywords: Amaranthus caudatus; Amaranthus cruentus; Amaranthus hypochondriacus; direct sowing; adaptation; agronomic characters